Evaluation of Antibacterial Activity of Ethanolic Fruit Extract of Cucumis trigonus Roxb. - Balakrishnan, A. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe present study investigates the antibacterial potential of ethanolic extract of the fruits of Cucumis trigonus. Cucumis trigonus Roxburghii of family Curcurbitaceae is a perennial scabrid monoecious tendrillar herb commonly used in Indian folklore medicine. The antibacterial activity was conducted on 4 bacterial species (Escherichia coli, Staphylococcus aureus, Bacillus cereus, Pseudomonas aeuriginosa) which normally seen in the urine of a urolithiatic infected person. The Paper disc diffusion method was used for the study. The ethanolic extract exhibited moderate activity against the bacterial strains as assessed by disc diffusion assays.